Palladium-Catalyzed Synthesis of Aromatic Sultones via Sulfonic Acid Group-Directed C--H Activation - 李飞 江桃山 蔡海婷 王官武 (Chinese journal of chemistry, 2012)
Aromatic sultones could be obtained by the palladium-catalyzed cyclization reaction of arylsulfonic acids with simple arenes. The reaction proceeds through sulfonic acid group-directed multiple C--H activations and involves the cleavage of C--H and O--H bonds as well as the formation of C--C and C--O bonds. Our protocol provides a facile access to aromatic sultones.